Character Development of Albus Dumbledore as Seen in J.K. Rowling’s Harry Potter Series - Mutiara Tita Trisnawijaya (Lexicon, 2015)
This research discusses the character development of Albus Dumbledore in Harry Potter series. The research is conducted within the framework of objective approach. The aim of this research is to analyze the development of Albus Dumbledore’s character throughout Harry Potter series.The data used in this research are taken from the seven novels of Harry Potter which contain Albus Dumbledore’s actions, other characters’ dialogues about Albus Dumbledore and author’s direct description. The data were classified in chronological order of Albus Dumbledore’s life and analyzed by using plot analysis. The result of the research depicts that Albus Dumbledore developed from an ambitious, immature and selfish character into a regretful, wise and protective character as he grew older. The development also shows that Albus Dumbledore has become a good brother, a wise leader and a protective mentor throughout the series.